Inclusive Education at Primary Level: Reality or Phantasm - Itfaq Khaliq Khan; Malik Ghulam Behlol (Journal of Education and Educational Development, 2014)
The objectives of this study were to assess the impacts of Inclusive Education (IE) Project implemented in government schools of Islamabad and anticipate its practicability for public schools. Quantitative and qualitative methods were applied for data collection. Study instruments were structured interviews, unstructured focus group discussions, and questionnaire. The study revealed that Students with Disabilities (SWDs) carrypositive attitudes about their mainstreaming and promote friendships among them. The accessibility of school infrastructure normally addresses the needs of all students, but curriculum, equipment, teaching, learning aids, and assessment methods need to be adjusted. Principals in the schools have a positive attitude towards IE and suggested the government take more concrete measures toward mobilizing financial and technical resources for the training of teachers and providing them with technological support. Teachers involved in IE practices have a positive attitude for inclusion of SWDs and they proposed that it can be replicated in all public schools.